Inhibition of Fibrinolysis in Post-Traumatic Death - Rammer, L; Saldeen, T (Thrombosis and Haemostasis, 1970)
The fibrinolytic system was studied in a number of autopsy cases. It was found that in contrast to most of the other autopsy cases those persons who had died later than 1 day after trauma, especially cases of fat embolism, often showed inhibition of fibrinolysis combined with the presence of intravascular fibrin in the pulmonary vessels. The importance of this observation for the pathogenesis and diagnosis of the fat embolism syndrome is discussed.